Fabrication and Characterization of DSSC/Si Tandem Solar Cell with PEDOT:PSS/ITO Buffer Layer (Journal of Solar Energy Research Updates, 2020)
In this study, dye-sensitized solar cell (DSSC)/silicon tandem solar cells were fabricated by changing the buffer layer structure. When joining two cells, a buffer layer is important to efficiently transport electrons by suppressing buffer of electrons by a potential barrier. Therefore, we used PEDOT:PSS/ITO as buffer layer structures, and measured their solar cell characteristics. As a result, it was found that the structure in which both PEDOT:PSS layer and ITO layer are stacked as buffer layers is suitable for the buffer layer of DSSC/Si tandem cells. In addition, the characteristics improved each time DMSO was added to PEDOT:PSS, and as a result, the characteristics of tandem solar cells also tended to improve. The maximum conversion efficiency (Voc = 0.78 V, Jsc = 4.87 mA / cm2, FF = 0.62, Eff = 2.35 %) was obtained when the DMSO concentration was 1%. It was suggested that conversion efficiency can be improved by improving the buffer layer.